Laparoscopic Trocar Port Site Endometriosis: A Case Report and Brief - Emre, A; Akbulut, S; Yilmaz, M; Bozdag, Z (2012)
Endometriosis is defined as the presence of ectopic endometrial tissue outside the lining of the uterine cavity. It occurs most commonly in pelvic sites such as ovaries, cul-de-sac, and fallopian tubes but also can be found associated with the lungs, bowel, ureter, brain, and abdominal wall. Abdominal wall endometriosis, also known as scar endometriosis, is extremely rare and mainly occurs at surgical scar sites. Although many cases of scar endometriosis have been reported after a cesarean section, some cases of scar endometriosis have been reported after an episiotomy, hysterectomy, appendectomy, and laparoscopic trocar port tracts. To our knowledge, 14 case reports related to trocar site endometriosis have been published in the English language literature to date. Herein, we present the case of a 20-year-old woman (who had been previously operated on for left ovarian endometrioma 1.5 years ago by laparoscopy) with the complaint of a painful mass at the periumbilical trocar site with cyclic pattern. Consequently, although rare, if a painful mass in the surgical scar, such as the trocar site, is found in women of reproductive age with a history of pelvic or obstetric surgery, the physician should consider endometriosis. C1 [Akbulut, Sami; Yilmaz, Mehmet] Inonu Univ, Dept Surg, Fac Med, TR-44280 Malatya, Turkey. [Emre, Arif] Malatya State Hosp, Dept Surg, Malatya, Turkey. [Bozdag, Zehra] Malatya State Hosp, Dept Pathol, Malatya, Turkey.